Diabetes-Related Health Care Utilization and Dietary Intake Among Food Pantry Clients - Eric M. Bomberg; Sophie Rosenmoss; Morgan Smith; Elaine Waxman; Hilary K. Seligman (Mary Ann Liebert, 2019)
Purpose: Consuming a diet appropriate for management of diabetes mellitus (DM) is challenging, particularly for adults with food insecurity (FI). DM-related health care services are thought to support better dietary intake. In this study, we explored associations between DM-related health care utilization and dietary intake among FI adults with DM. Methods: We used cross-sectional, baseline data (collected 2015?2016) from a trial designed to improve glycemic control among adult food pantry clients with DM. We examined intake of vegetables, fruit, sugar-sweetened beverages (SSBs), and desserts using the California Health Interview Survey dietary screener. We then examined adjusted associations between dietary intake and two components of DM-related health care utilization (<12 months vs. ?12 months ago): self-reported visit to a health care provider for DM management and DM self-management education. Results: Among 523 participants (mean hemoglobin A1c 9.8%; body mass index 34.6?kg/m2; 17.0% uninsured), vegetable intake was more frequent in those reporting recent utilization of health care providers for DM management and DSME-related services (p<0.01), compared with those with less recent use. There was no association between intake frequency of fruit or SSBs and utilization of either DM-related service. Participants more recently utilizing DSME-related services consumed desserts more frequently (p=0.02). Relationships persisted after controlling for DM duration, race/ethnicity, education, health insurance, location, medication adherence, and depression. Conclusions: Among FI patients, DM-related services offered in clinical settings may more effectively increase vegetable consumption than decrease consumption of food and beverage items that can worsen glycemic control. Food pantry settings may provide an opportunity to reinforce dietary messaging.